2024 Symposium on African Digital Humanities: Digital Humanities, African Stories, and Agency - Darkwah, A.; Ocloo, P.E.D.; Opoku-Agyemang, K.; Rosenblum, B.; Yeku, J. (My University, 2024)
The symposium particularly welcomes graduate students and early-career faculty interested in digital humanities and will provide stipends for graduate students in the region to attend. The 2024 symposium seeks to stimulate a dialogue that addresses the intersections of the digital humanities and African stories and agency. We will explore digital storytelling and its connections to African narratives, the extractive politics of platform, AI and African agency, as well as diverse approaches and issues related to building an inclusive digital cultural record for local and global communities.
Symposium
Keywords: Digital Humanities; African; Stories; AI